Vom antiautoritären Kindermärchen zum postmodernen Film? Die Verwandlungen des Sams - Neuhaus, Stefan (Revista de Filología Alemana, 2007)
One of the most popular children’s characters in Germany is called the ‘Sams’. The well-known author Paul Maar wrote the first Sams book in 1973 and helped to transform it into a successful film in 2001, starring the popular German actor Ulrich Noethen as Mr. Taschenbier who has many problems looking after the Sams. A sequel Sams in Gefahr (Sams in Danger) was made in 2003. The books and films about the Sams can be regarded as an example of the possibilities and limitations of transforming literature into film. Can a good children’s movie live up to the expectations that the readers have of a popular series of books? And what is a good children’s movie?